RIPHEAN SEDIMENTARY SEQUENCES OF THE EASTERN AND NORTHEASTERN MARGINS OF THE EASTERN EUROPEAN CRATON - Maslov A.V.; Isherskaya M.V. (My University, 2002)
The Riphean history of depositional basins in the study region can be divided into Early-Middle Riphean and Late Riphean phases. Throughout the Riphean, clastic material was supplied chiefly from eastern regions of the Russian craton. Deposition occurred mainly in semi-arid environments, humid and near-glacial epochs being considerably shorter. Riphean carbonate and siliciclastic sedimentary deposits are dominated by those of shallow-water and nearshore basin environments. In the Early and Middle Riphean, the principal type of depositional basins in the study region was relatively small epicratonic seas. The peculiarities of architecture and spatial distribution of the Late Riphean sedimentary deposits suggest that in the middle or end of this timespan, there appeared a major cratonic-margin basin that covered the entire eastern and northeastern margins of the Eastern European craton.
Keywords: RIPHEAN SEDIMENTARY SEQUENCES; EASTERN EUROPEAN CRATON; SEDIMENTARY DEPOSITS; Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей